Revamping the Roles of Non-State Policing Actors: An Appraisal of KAROTA in Kano Metropolis - BARJE, Timothy Zakimayu; ABEDO, Abdussalam Umar (Nigerian Journal of Peace, Development & Humanitarian Affairs, 2023)
The challenges of everyday policing in a large commercial city like Kano makes it expedient for the state government to consider alternative solutions using non-state policing actors in maintaining law and order. The popularity of non-state policing actors is fast becoming acceptable even amongst state governors who exploit the opportunity to establish those using state laws for specific functions. By looking at the establishment and activities of the Kano Roads and Transport Agency (KAROTA), this research aims to examine how non-state policing groups are instrumental in maintaining law and order within the Kano metropolis. Being residents of Kano when KAROTA was newly established, the authors relieved some of their experiences in writing the research, coupled with interviews conducted with other residents, agents and administrators of the agency and some newspaper reports. It concludes that with proper handling some of the negative tendencies of KAROTA can be corrected and the agency aligned for greater services.